KESANTUNAN TINDAK TUTUR NAJWA SHIHAB DALAM GELAR WICARA MATA NAJWA DI EPISODE 100 HARI ANIES-SANDI - Falia, Kaka Yuni Rizky; Thahar, Harris Effendi; Tressyalina, Tressyalina (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACTÂ There are four purposes of the act of saying Najwa Shihab in this research. First, describe the act of speech illocution. Second, describe the strategy of speech acts. And third, describes the principle of politeness. This research type is qualitative research by using descriptive method. The data of this research is Najwa Shihab's speech which is in the form of words in Mata Najwa Speech title in the 100-day Anies-Sandi episode. The instrument is the researcher himself. Data collection techniques there are three. First, the researchers downloaded the first Mata Najwa video titles in the 100-day Anies-Sandi episode in the Official Najwa Shihab account on youtube.com. Secondly, Najwa Shihab's speech data is transcribed. And thirdly, the researcher performs inventory of data. The next step is to analyze the research data through the following techniques. First, classify the data based on politeness. Second, to analyze the data obtained. Third, make inferences to the data based on the results of analyzing the data.Â Kata kunci: kesantunan, tindak tutur, Najwa Shihab, gelar wicara